2019
DOI: 10.1007/s12311-019-01063-z
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Physical Therapy Interventions for Children with Ataxia: A Systematic Review

Abstract: The effectiveness of exercise and physical therapy for children with ataxia is poorly understood. The aim of this systematic review was to critically evaluate the range, scope and methodological quality of studies investigating the effectiveness of exercise and physical therapy interventions for children with ataxia. The following databases were searched: AMED, CENTRAL, CDSR, CINAHL, ClinicalTrials.gov, EMBASE, Ovid MEDLINE, PEDro and Web of Science. No limits were placed on language, type of study or year of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 76 publications
(175 reference statements)
0
15
0
1
Order By: Relevance
“…Standard prevention and treatment for obesity and metabolic syndrome include a healthy diet/caloric intake and exercise, although several factors associated with WAGR syndrome can present challenges to these standard therapies, supporting the need for a multidisciplinary care team approach. Approximately a quarter of participants in the WAGR Discovery Cohort reported ataxia, which can lead to a variety of functional difficulties that complicate normal exercise, such as balance and walking issues and a recent systematic review found that evidence is lacking related to the effectiveness of physical therapy and exercise interventions for children with ataxia ( 52 ). Additionally, a substantial portion of participants reported issues with hypo- or hypertonia, toe-walking, spasticity, and scoliosis which highlights the need for neurological and orthopedic evaluations to determine whether any issues are present that could affect the ability to exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Standard prevention and treatment for obesity and metabolic syndrome include a healthy diet/caloric intake and exercise, although several factors associated with WAGR syndrome can present challenges to these standard therapies, supporting the need for a multidisciplinary care team approach. Approximately a quarter of participants in the WAGR Discovery Cohort reported ataxia, which can lead to a variety of functional difficulties that complicate normal exercise, such as balance and walking issues and a recent systematic review found that evidence is lacking related to the effectiveness of physical therapy and exercise interventions for children with ataxia ( 52 ). Additionally, a substantial portion of participants reported issues with hypo- or hypertonia, toe-walking, spasticity, and scoliosis which highlights the need for neurological and orthopedic evaluations to determine whether any issues are present that could affect the ability to exercise.…”
Section: Discussionmentioning
confidence: 99%
“…231 However, treatment should depend on the disease and the impairments. For instance, it is not clear whether exercise can be helpful in children with ataxia, 275 and strengthening exercises may not be manifestly effective in adult patients with Charcot-Marie-Tooth disease, 276 whereas adapted training can be helpful. 277 Endurance and balance training seem to be effective in chemotherapyinduced peripheral neuropathies.…”
Section: Other Neuropathies and Balancementioning
confidence: 99%
“…Physical therapy, home exercise programs (including stretching, core strengthening, balance, and cardio), occupational therapy, speech and swallowing therapy, weighted vests [8], orthotics, assistive equipment assessment, home safety evaluations, and driving evaluations can all improve patient and family quality of life and safety, reduce falls, and help maintain patient independence [9,10]. Home Health organizations can provide these resources, as well as nursing and social work assistance, for the homebound.…”
Section: Rehabilitationmentioning
confidence: 99%